Effectiveness of cognitive-behavioural therapy for obsessive-compulsive disorder in children and adolescents: a qualitative review - Rosa Alcazar, Ana Isabel; Iniesta Sepúlveda, Marina; Rosa Alcázar, Angel (Anales de Psicología / Annals of Psychology, 2012)
This paper presents the results a qualitative review study on effectiveness of cognitive-behavioural therapy for obsessive-compulsive disorder in children and adolescents. A total of 84 studies were located and retrieved, of which 17 were case reports, 37 were single case designs, 19 were quasi-experimental one-group studies, 6 were quasi-experimental comparison studies and 5 randomized controlled trials. The most widely treatment procedure, in the studies, was exposure with response prevention, which also was the most effective. We found a low representation of comparison studies, both quasi-experimental and experimental designs, as well as a lack of medium and long-term follow-ups, observational measures and a poor control of covert symptomatology and comorbidity.